Integrated Science Education Mobile Application: Edukit for 21st Century Students - Erni Yulianti; Desta Wahyu Maharani; Erti Hamimi (Universitas Muhammadiyah Sidoarjo, 2021)
The aim of this study is to develop a valid and practical science learning media that integrated with mobile application (EduKIT). This EduKIT provide activities so students can have experiences to string and think solution about any problems integrated by technology as demanded of Education in 21st century. This research using ADDIE model which is only limited to the development stage. At each stage, an evaluation process is carried out to produce the maximum product. To measure the validity and feasibility of the media, an instrument in the form of a questionnaire was used. Quantitative data is obtained from the score given by the validator against each criterion and indicator on the validation sheet. While the qualitative data is obtained from the advice given by the validator. The result shows that the EduKIT was highly valid to use with the percentage 98% and 99% for validation media and content validity respectively. This assessment was tested on two science education experts. While the result for the readability test by five teachers was 96% and 91% from ten junior students. Those percentage (>90%) show very practical and highly valid to be used. Based on the results of the validation and readibility test, it can be concluded that EduKIT was valid and practical, so it is suitable for students to use as a learning medium to practice problem solving skills in preparing the 21st century generation.